Does performance management affect nurses' well-being?. (April 2015) - Decramer, Adelien; Audenaert, Mieke; Van Waeyenberg, Thomas; Claeys, Tine; Claes, Claudia; Vandevelde, Stijn; van Loon, Jos; Crucke, Saskia
Abstract: Aim: This article focuses on employee performance-management practices in the healthcare sector. We specifically aim to contribute to a better understanding of the impact of employee performance-management practices on affective well-being of nurses in hospitals. Theory suggests that the features of employee-performance management (planning and evaluation of individual performances) predict affective well-being (in this study: job satisfaction and affective commitment). Methods: Performance-management planning and evaluation and affective well-being were drawn from a survey of nurses at a Flemish hospital. Separate estimations were performed for different aspects of affective well-being. Results: Performance planning has a negative effect on job satisfaction of nurses. Both vertical alignment and satisfaction with the employee performance-management system increase the affective well-being of nurses; however, the impact of vertical alignment differs for different aspects of affective well-being (i.e. job satisfaction and affective commitment). Conclusion: Performance-management planning and evaluation of nurses are associated with attitudinal outcomes. The results indicate that employee performance-management features have different impacts on different aspects of well-being.